Previremic Identification of Ebola or Marburg Virus Infection Using Integrated Host-Transcriptome and Viral Genome Detection - Emily Speranza (American Society for Microbiology, 2020)
ABSTRACT Outbreaks of filoviruses, such as those caused by the Ebola (EBOV) and Marburg (MARV) virus, are difficult to detect and control. The initial clinical symptoms of these diseases are nonspecific and can mimic other endemic pathogens. This makes confident diagnosis based on clinical symptoms alone impossible. Molecular diagnostics for these diseases that rely on the detection of viral RNA in the blood are only effective after significant disease progression. As an approach to identify these infections earlier in the disease course, we tested the effectiveness of viral RNA detection combined with an assessment of sentinel host mRNAs that are upregulated following filovirus infection. RNAseq analysis of EBOV-infected nonhuman primates identified host RNAs that are upregulated at early stages of infection. NanoString probes that recognized these host-response RNAs were combined with probes that recognized viral RNA and were used to classify viral infection both prior to viremia and postviremia. This approach was highly successful at identifying samples from nonhuman primate subjects and correctly distinguished the causative agent in a previremic stage in 10 EBOV and 5 MARV samples. This work suggests that unified host response/viral fingerprint assays can enable diagnosis of disease earlier than testing for viral nucleic acid alone, which could decrease transmission events and increase therapeutic effectiveness. IMPORTANCE Current molecular tests that identify infection with high-consequence viruses such as Ebola virus and Marburg virus are based on the detection of virus material in the blood. These viruses do not undergo significant early replication in the blood and, instead, replicate in organs such as the liver and spleen. Thus, virus begins to accumulate in the blood only after significant replication has already occurred in those organs, making viremia an indicator of infection only after initial stages have become established. Here, we show that a multianalyte assay can correctly identify the infectious agent in nonhuman primates (NHPs) prior to viremia through tracking host infection response transcripts. This illustrates that a single-tube, sample-to-answer format assay could be used to advance the time at which the type of infection can be determined and thereby improve outcomes.